Answer:
![\large\boxed{A=x^2+23x+49}](https://img.qammunity.org/2020/formulas/mathematics/high-school/vactxco9pflmkwm1p39hl8o20osdhlos8m.png)
Explanation:
Subtract the area of a square (x + 1) × (x + 1)
from the area of a rectangle (x + 10) × (2x + 5)
The area of a square:
use FOIL: (a + b)(c + d) = ac + ad + bc + bd
![A_s=(x)(x)+(x)(1)+(1)(x)+(1)(1)=x^2+x+x+1=x^2+2x+1](https://img.qammunity.org/2020/formulas/mathematics/high-school/s9lk80j01fsz9vchsl5idzxf7dve7jt2ut.png)
The area of a rectangle:
use FOIL
![A_r=(x)(2x)+(x)(5)+(10)(2x)+(10)(5)=2x^2+5x+20x+50=2x^2+25x+50](https://img.qammunity.org/2020/formulas/mathematics/high-school/1pdipxisqk2h0t3dsk4e885c0praz69coq.png)
The area of a figure:
![A=A_r-A_s](https://img.qammunity.org/2020/formulas/mathematics/high-school/d05mjy0nlzsnae1eex5bkwv1dkudsz7zv6.png)
Substitute:
![A=(2x^2+25x+50)-(x^2+2x+1)=2x^2+25x+50-x^2-2x-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/mxsjrzblyn0olyjul43i29bdilqjkhn7j6.png)
combine like terms
![A=(2x^2-x^2)+(25x-2x)+(50-1)=x^2+23x+49](https://img.qammunity.org/2020/formulas/mathematics/high-school/x19dj1ey64c4bviy5s9snt1ttpxfzawdwl.png)